2009
DOI: 10.1002/hipo.20586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neonatal stress on markers of synaptic plasticity in the hippocampus: Implications for spatial memory

Abstract: Early stressful adverse situations may increase the vulnerability to cognitive deficits and psychiatric disorders, such as depression. Maternal separation (MS) has been used as an animal model to study changes in neurochemistry and behavior associated with exposure to early-life stress. This study investigated the effects of neonatal stress (MS) on the expression of synaptic plasticity markers in the hippocampus and a purported relationship to cognitive processes. Spatial learning (Morris water maze) significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(126 citation statements)
references
References 92 publications
(108 reference statements)
9
115
0
1
Order By: Relevance
“…However, in the current experiment we have not found differences in the levels of 5-methylcytosine immunostaining in hippocampus between MS and control animals. Our group has previously reported a significant decrease in hippocampal BDNF expression in the same rat model of 3-hour daily maternal separation [44]. A recent study has reported that methyl supplementation via methionine is able to increase BDNF DNA methylation and reduce BDNF mRNA levels in the hippocampus of epileptic rats during memory consolidation, reversing memory deficits in these animals [45].…”
Section: Discussionmentioning
confidence: 78%
“…However, in the current experiment we have not found differences in the levels of 5-methylcytosine immunostaining in hippocampus between MS and control animals. Our group has previously reported a significant decrease in hippocampal BDNF expression in the same rat model of 3-hour daily maternal separation [44]. A recent study has reported that methyl supplementation via methionine is able to increase BDNF DNA methylation and reduce BDNF mRNA levels in the hippocampus of epileptic rats during memory consolidation, reversing memory deficits in these animals [45].…”
Section: Discussionmentioning
confidence: 78%
“…Prenatal stress and maternal separation even decreases the size and complexity of the new neurons that are born in adulthood in the dentate gyrus (Leslie et al, 2011;Tamura et al, 2011). Stress during the early postnatal period produced by maternal separation reduces cell proliferation, neurogenesis, and the survival of new neurons in adult rodents in the dentate gyrus (Aisa et al, 2009;Leslie et al, 2011;Mirescu et al, 2004;Sachs et al, 2013).…”
Section: Effects Of Early-life Experiences On Adult Neurogenesis and mentioning
confidence: 99%
“…Protein concentration for each sample was estimated as previous [42]. NCAM levels were quantified according to a previously described protocol [25]. Flat bottom 96-well microplates were allowed to adsorb a coating solution (Na 2 CO 3 0.1 M/ NaHCO 3 , 0.1 M) for 2 h at room temperature.…”
Section: Quantification Of Total Levels Of Ncammentioning
confidence: 99%
“…NCAM can be also modified by the addition of α-2,8-polysialic acid (PSA-NCAM). At the systems level, NCAMs have been implicated as critical components in the induction of long-term potentiation (LTP) and in memory formation [20,21] NCAMs have been shown to play critical roles in ontogenetic development and are thus potential candidates in expression of age-related pathology, particularly in AD [24,25].…”
Section: Introductionmentioning
confidence: 99%